Attitudes of European citizens towards climate change: A gender analysis - Mata, F; Dos-Santos, M. (Proceedings of the 20th European Conference on Management Leadership and Governance, ECMLG 2024, 2024)
The present paper analyses attitudes and perceptions regarding climate change (CC) among European citizens, emphasizing their pivotal role in fostering public engagement and endorsement towards the advancement of mitigatory measures and sustainable lifestyles in accordance with the United Nations’ Sustainable Development Goals. This study delves into the degree of concern among European citizens regarding CC and their inclination towards assuming personal accountability in its alleviation, scrutinizing these facets through gender attitudes. Utilizing data from the European Social Survey and information on attitudes and perceptions about CC, the analysis incorporates various variables encompassing socio-economic status, demographics, individual perceptions of societal dynamics, and governmental policies. Employing econometric methodologies, the results confirm that individuals exhibiting trust in scientific authority manifest heightened concerns towards CC. Moreover, those expressing contentment with national governance display augmented levels of concern regarding CC. Gender differentials are also discernible, with females exhibiting greater apprehension towards CC than males. Furthermore, advanced age and higher educational attainment correlate with heightened levels of CC concern. Additional findings indicate that females tend to exhibit greater proclivity towards assuming self-responsibility, while individuals harbouring trust in scientific authority evince heightened levels of personal accountability, particularly when content with economic stability and the efficacy of the country's healthcare system. Additionally, older individuals who trust scientific expertise tend to exhibit greater proclivity towards assuming personal responsibility. The findings underscore the imperative of comprehending the gendered ramifications of climate change and advocating for collective endeavours to combat this pervasive global challenge.